2001
DOI: 10.1021/jm0005510
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Photophysical Properties, Tumor Uptake, and Preliminary in Vivo Photosensitizing Efficacy of a Homologous Series of 3-(1‘-Alkyloxy)ethyl-3-devinylpurpurin-18-N-alkylimides with Variable Lipophilicity

Abstract: Starting from methylpheophorbide-a, a homologous series of purpurinimides containing alkyl substituents at two different positions [as 3-(1(1)-O-alkyl) and 13(2)-N-alkyl] were synthesized. These compounds with variable lipophilicity (log P 5.32-16.44) exhibit long wavelength absorption near lambda(max)700 nm (epsilon: 45 000 in dichloromethane) with singlet oxygen ((1)O2) production in the range of 57-60%. The shifts in in vivo absorptions and tumor/skin uptake of these compounds were determined in C3H mice be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(84 citation statements)
references
References 20 publications
(21 reference statements)
0
78
0
6
Order By: Relevance
“…This allowed the synthesis of an extensive glycoporphyrin library which has been biologically evaluated and used to identify the intracellular localization of glycoporphyrins depending on the carbohydrate unit present [33] . For example, these preliminary results in biological testing showed that triglycosubstituted porphyrins lack the ability to be taken up by esophageal cancer cells possibly due to their high water solubility and reinforced that amphiphilicity of such systems is key to their ability to cross the lipid membrane [34][35][36][37][38][39][40][41][42] .…”
Section: Carbohydratesmentioning
confidence: 99%
“…This allowed the synthesis of an extensive glycoporphyrin library which has been biologically evaluated and used to identify the intracellular localization of glycoporphyrins depending on the carbohydrate unit present [33] . For example, these preliminary results in biological testing showed that triglycosubstituted porphyrins lack the ability to be taken up by esophageal cancer cells possibly due to their high water solubility and reinforced that amphiphilicity of such systems is key to their ability to cross the lipid membrane [34][35][36][37][38][39][40][41][42] .…”
Section: Carbohydratesmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41] Показано, что такая модификация не только улучшает их растворимость, но и в ряде случаев приводит к увеличению их сенсибилизирующей активности. Ченг и Пандей, [15] синтезируя циклоимиды из метилового эфира пурпурина 18 1b и гексиламина в присутствии кислоты Льюиса и гексаметилдисилазана обнаружили, что в процессе реакции одновременно с образованием имидного цикла происходит замещение метоксикарбонильной группы в остатке пропионовой кислоты на амид. Основным продуктом в этих условиях является 17 2 -N-гексиламид N-гексилциклоимида 10.…”
Section: химические превращения карбоксильной группы остатка пропионоunclassified
“…[13] впервые показали, что амидные производные пурпурина 18, полученные раскрытием ангидридного кольца под действием алкиламинов, могут образовывать имидные аналоги, если реакционную массу оставить при комнатной температуре на несколько недель. Позднее Ченг и Пандей [14][15][16] разработали метод получения подобных соединений с варьируемой липофильностью. При обработке пурпурина 18 1 различными алкиламинами (C 1 -C 11 ) [13,17,18] в хлористом метилене при комнатной температуре образуется смесь соответствующих амидов 2 и 3 (Схема 1) в соотношении 6:1 с общим выходом 95%.…”
Section: Introductionunclassified
See 2 more Smart Citations